Temporal characteristics of microwave radiations emitted during stepped leaders process of negative ground flashes - Shamsul Baharin, Shamsul Ammar (2021)
Electrical breakdown is a mechanism that initiate lightning flash and consists of electron avalanches, streamers, and leader processes. The lightning type that brings down negative charges to ground is called negative cloud-to-ground (-CG) flash. The -CG flash starts with initial breakdown (IB) followed by stepped leader (SL) and return stroke (RS) processes. In this thesis, temporal characteristics of microwave and Very High Frequency (VHF) electric field radiations associated with SL process are studied. Stepped leader is an example of conventional breakdown that consists of a special pilot system called space stem that can develops into bidirectional streamer. This study is driven by motivation to understand whether both microwave and VHF radiations are radiated by the same process or not. The VHF radiation is known to be associated with propagating streamer. In literature, propagating streamer is the source of VHF radiation emission while sources of microwave radiation from lightning are from the head-on collisions of streamers and electron avalanche/corona breakdown at the tip of leader. Therefore, this study aimed to design and deploy a measurement system to measure both the microwave and VHF radiations associated with SL process. Then, the collected electric field data are analyzed in time domain to evaluate the relationship between microwave and VHF radiations and electron avalanches and corona breakdown process. The measurement set up consists of four sensors namely fast antenna (FA) (10 Hz to 3 MHz), slow antenna (SA) (1 Hz to 1 kHz), microwave (0.97 GHz) and VHF (60 MHz) systems. A total of ten very close -CG flashes (within reversal distance) accompanied by both VHF and microwave radiations have been chosen and analyzed. Moreover, to validate the existence of lightning thunderstorm on the day of the measurement campaign, the collected data are compared with Tenaga Nasional Berhad Research (TNBR) lightning locations. The first significant analysis is that all microwave radiations were observed to lead SL process with average leading time of 0.423±0.378 µs and around 80.41% of microwave radiation bursts lead VHF radiation bursts with average leading time of 0.540±0.596 µs. The second significant analysis is that microwave radiation temporal characteristics can be classified into three categories during Quiet Period (QP). The first category consists of two microwave bursts during QP while second category has one microwave burst only. For Category 3, no microwave burst detected. The first and second microwave bursts of Category 1 are suggested to be associated with electron avalanches and corona breakdown at the tip of negative leader and space stem, respectively. Microwave burst in Category 2 is suggested to be radiated by electron avalanches and corona breakdown at the tip of negative leader while space stem was absent. As space stem process was absent the QP duration in Category 2 is shorter than Category 1, 2.319 µs compared to 4.573 µs, respectively. In Category 3, the detected VHF burst is suggested to be emitted by upward propagating positive streamers. To conclude, the analyses done in this study provide strong suggestion that microwave and VHF radiations are emitted by different breakdown process.